Simplifying contact-layer design for high-throughput printing of flexible perovskite photovoltaics - Dong, Lirong; Qiu, Shudi; Feroze, Sarmad; Wagner, Michael; Kasian, Olga; Peisert, Heiko; Kosasih, Felix U.; Ducati, Caterina; García Cerrillo, José; Tian, Jingjing; Li, Chaohui; Jang, Dongju; et al. (Energy and Environmental Science, 2024)
The realization of scalable roll-to-roll production processes for metal-halide perovskite modules is a necessary development for transferring developments and technologies from the lab to the fab. Before that, it is imperative to close the efficiency gap not only between the devices fabricated on rigid substrates versus flexible substrates, but also between solar cells to solar modules. In this regard, a critical assessment of device architectures that are more compatible to scalable fabrication is needed. Obviously, the adaption to mass manufacturing must not negatively impact device performance and operational stability. Here, by investigating the properties of printed fullerene-based phosphonic acid dipole interface layers, we establish simplified self-assembled monolayer (SAM) based n-i-p architectures without any charge extraction layers other than SAMs, which are easily processed and are thus ideally suited for mass production. We show that a contact-layer design with a printed fullerene-based SAM that has phosphonic acid is sufficient to provide good charge selectivity and to minimize interface recombination at the bottom electrode. We further show that the same SAM molecule can be used as a p-type interface material on top of the perovskite. This simplified contact-layer design, which is based on one material for both hole and electron work-function adaption is successfully integrated into our fully printed module process comprising the deposition of a carbon top electrode. The achieved open-circuit voltage exceeds 1.1 V, and the fill factor surpasses 70%, highlighting the potential of this novel interface design concept for both rigid and flexible substrates.
CRIS-Team Scopus Importer:2024-09-06